Answer:
![P(t) = 104.267\ millions](https://img.qammunity.org/2020/formulas/mathematics/college/4wqimlz58652xlrhky0kwhabjs6l9gu6ie.png)
Explanation:
The exponential growth formula is
![P(t) = Ae^(kt)](https://img.qammunity.org/2020/formulas/mathematics/college/ya6h02ipfwwp4bncpleraww5vkwwjpody0.png)
Where
A is the main coefficient and represents the initial population.
e is the base
k is the growth rate
t is time in years.
Let's call t = 0 to the initial year 1993.
At t = 0 the population was 94 millions
Therefore we know that:
millions
After t = 6 years, in 1996, the population was 99 millions.
Then
million.
Now we use this data to find the variables a, and k.
.
Then:
![P(6) = 94e^(k(6))\\\\99 = 94e ^(6k)\\\\(99)/(94) = e^(6k)\\\\ln((99)/(94)) = 6k\\\\k = (ln((99)/(94)))/(6)\\\\k =0.008638](https://img.qammunity.org/2020/formulas/mathematics/college/sq8uvfn7x6dewnhkr3kjemu0dwt5aaon72.png)
Finally the function is:
![P(t) = 94e^(0.008638t)](https://img.qammunity.org/2020/formulas/mathematics/college/1fwuk5etblo9wsitcw2umvomw4yhh7kmg7.png)
In the year 2005:
![t = 2005-1993\\\\t= 12\ years](https://img.qammunity.org/2020/formulas/mathematics/college/2ws6qejdfcxqjcukml7bvdhvtbb7xb7psi.png)
So the population after t=12 years is:
![P(t) = 94e^(0.008638(12))](https://img.qammunity.org/2020/formulas/mathematics/college/ns8erw0oq0e1imzte2iwnu68q1tmv2s37w.png)
![P(t) = 104.267\ millions](https://img.qammunity.org/2020/formulas/mathematics/college/4wqimlz58652xlrhky0kwhabjs6l9gu6ie.png)